Heat and salinity stress on the African eggplant F1 Djamba, a Kumba cultivar - David-Rogeat, Noémie; Broadley, Martin R.; Stavridou, Eleftheria (Frontiers in Plant Science, 2024)
Climate change is expected to increase soil salinity and heat-wave intensity, duration, and frequency. These stresses, often present in combination, threaten food security as most common crops do not tolerate them. The African eggplant (Solanum aethiopicum L.) is a nutritious traditional crop found in sub-Saharan Africa and adapted to local environments. Its wider use is, however, hindered by the lack of research on its tolerance. This project aimed to describe the effects of salinity (100 mM NaCl solution) combined with elevated temperatures (27/21°C, 37/31°C, and 42/36°C). High temperatures reduced leaf biomass while cell membrane stability was reduced by salinity. Chlorophyll levels were boosted by salinity only at the start of the stress with only the different temperatures significantly impacting the levels at the end of the experiment. Other fluorescence parameters such as maximum quantum yield and non-photochemical quenching were only affected by the temperature change. Total antioxidants were unchanged by any stress despite a decrease of phenols at the highest temperature. Leaf sodium concentration was highly increased by salinity but phosphorus and calcium were unchanged by this stress. These findings shed new light on the tolerance mechanisms of the African eggplant under salinity and heat.Further research on later developmental stages is needed to understand its potential in the field in areas affected by these abiotic stresses.